Pendampingan Penetapan Harga Jual Produk dengan Pemilihan Perhitungan Harga Pokok Penjualan sebagai Dasar Penentuan pada UMKM Makanan di Daerah Setu Babakan - Alhabsyi, Zulfa; Meilani, Tantri; Azizah, Wafiq; Rahmadanti, Erinda; Hardinah, Siti; Rahmadi, Zara Tania (ASOSIASI IDEBAHASA KEPRI, 2025)
Serving the community is an activity that involves training and mentoring in calculating the cost of goods sold for Babeh Nur's Nasi Bakar MSME. This MSME was established in 2018 by the owner himself with help from neighbors around the house(Yunaz et al., 2020). As an economic operator who develops a product by himself, one must know the production cost of a product according to the production cost formula. Assessing production costs helps in improving the understanding of micro, small, and medium entrepreneurs who are directly involved in their production process. In this study, data was collected using the standard method through a survey to the owner of Nasi Bakar Babeh Nur MSME. Objectives From this activity, we only want to gain an understanding of how production costs at MSME Nasi Bakar Babeh Nur are calculated. We hope that after the training program, input data and information related to the calculation of production costs in accordance with the accounting system will be available for use by business actors.